Clinical value of combined predictors of RET%, γ-GT, LDH in the ABO neonatal hemolytic disease - Liu, Xiaoxiao; Dong, Yan; Qin, Yingchao; Xue, Chunyan; Lyu, Wei (Frontiers in Pediatrics, 2023)
The purpose of this study is to examine the prognostic significance of the amalgamated indicators, reticulocyte percentage (RET%), lactate dehydrogenase (LDH), and γ-Glutamyltransferase (γ-GT), in neonatal ABO hemolytic disease.Methods: A total of 137 hospitalized children with pathological jaundice were included.Based on their medical conditions, they were categorized into two groups, hemolytic (67 cases) and non-hemolytic (70 cases). Pearson linear correlation and binary logistic multivariate analysis were used to analyze LDH, γ-GT, RET% and hemolysis.Furthermore, the predictive value of the combined predictors of RET%, LDH, and γ-GT on ABO neonatal hemolytic disease was evaluated using the ROC curve analysis.The laboratory indexes of the two groups were subject to analysis using binary logistic regression to identify suspicious influencing factors. The study revealed that RET%, LDH, and γ-GT were independent risk factors for hemolysis. Pearson linear correlation analysis indicated a positive correlation between LDH and γ-GT with RET% (r=0.529, P<0.01; r=0.526, P= <0.01, respectively). Furthermore, the predictive value of each combined predictor was obtained using the ROC curve, and it was observed that combined predictor L (RET% + LDH+ γ-GT)＞L1 (RET%+ LDH)＞L2 (RET%+ γ-GT).Combined predictor L (RET% + LDH+ γ-GT)demonstrate its optimal diagnostic efficacy, offering a novel approach towards diagnosing early-onset ABO hemolytic disease of the newborn.